The association between heightened ADHD symptoms and cytokine and fatty acid concentrations during pregnancy - Gustafsson, Hanna C.; Dunn, Geoffrey A.; Mitchell, A. J.; Holton, Kathleen F.; Loftis, Jennifer M.; Nigg, Joel T.; Sullivan, Elinor L. (Frontiers in Psychiatry, 2022)
Objective: Previous research conducted with samples of children suggest that individuals with attention-deficit/hyperactivity disorder (ADHD) have altered fatty acid concentrations and may have increased systemic inflammation. Whether these differences are also apparent in other populations of individuals with heightened ADHD symptoms (e.g., pregnant adults) is unknown. The goal of the current study was to examine whether there are ADHD-associated differences in polyunsaturated fatty acid concentrations or pro-inflammatory cytokine concentrations during pregnancy, a developmental period when fatty acid concentrations and systemic inflammation have implications for the health of both the pregnant person and the developing child. We hypothesized that plasma levels of the ratio of omega-6s to omega-3s (n-6:n-3) and plasma inflammatory cytokine levels would be higher in individuals with heightened ADHD symptoms, consistent with previous findings in children with ADHD. Methods: Data (N=68) came from a prospective study of pregnant community volunteers who were oversampled for ADHD symptoms. During the 3rd trimester, plasma concentrations of fatty acids and the pro-inflammatory cytokines interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) were assessed. Dietary intake was examined in the 3rd trimester using three 24-hour recalls conducted by trained dietitians and by examining plasma levels of conjugated linoleic acid (n-6) and α-linolenic acid (n-3), essential fatty acids that must come from dietary intake. Results: The group with heightened ADHD symptoms had higher n-6:n-3s (β=.30, p<.01) and higher TNF-α concentrations (β =.35, p<.001) relative to controls. There were no group differences in dietary variables, as assessed by self-report and via plasma concentrations of essential fatty acids. IL-6 was not reliably associated with ADHD status in this sample. Conclusions: Pregnant individuals with ADHD, on average, had higher plasma n-6:n-3s and higher TNF-α concentrations relative to controls. A difference was not detected in their dietary intake of fatty acids or other relevant nutrients. Though these null findings are inconclusive, they are consistent with the hypothesis that ADHD-associated differences in plasma fatty acid concentrations are the result of ADHD-associated differences in fatty acid metabolism, rather than simply differences in dietary intake.